A Post-doctoral Project on Inclusive Education in Greece and Cyprus: From Pedagogical Research to New Educational Challenges - Vasiliki Ioannidi; Konstantinos D. Malafantis (An Overview of Literature, Language and Education Research Vol. 5, 2024)
This paper presents a brief report on a postdoctoral project based on Inclusive Education in the international Greek-speaking area (Greece and Cyprus). The postdoctoral study focuses on understanding the complex frame of inclusion, empowering the inclusive teacher and the skills driving inclusive education. The central research questions guiding this project were: What is the conceptual definition of Inclusive Education? What pedagogical and instructional methods of learning and education are viable for inclusivity? What knowledge and skills are required by modern Inclusive Teachers for an inclusive school? The purpose of the project was: To create a theoretical, empirical and applied research framework for Inclusive Education. So, a list of guidelines and principles was selected based on international literature and reviews. Also, the empirical investigation is based on teachers’ views on the skills required for inclusive education. According to findings, creative, collaborative, communication, digital and ethical skills are required for an inclusive teacher in blended educational environments. This postdoctoral research contributes to the discourse on Inclusive Education and highlights the importance of skills in inclusive learning environments focusing on innovation of E-tivities in blended learning. Its contribution can lead to a deeper understanding of inclusive classrooms, inspire further studies and potentially influence practical applications or policy decisions in the field of Inclusivity.